Severe pediatric acute encephalopathy syndromes related to SARS-CoV-2 - Sakuma, Hiroshi; Takanashi, Jun-ichi; Muramatsu, Kazuhiro; Kondo, Hidehito; Shiihara, Takashi; Suzuki, Motomasa; Okanari, Kazuo; Kasai, Mariko; Mitani, Osamu; Nakazawa, Tomoyuki; Omata, Taku; Shimoda, Konomi; et al. (Frontiers in Neuroscience, 2023)
Background and objectives To clarify whether severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection cause acute encephalopathy in children and which are the most common syndromes that cause them and what are the outcomes. Methods A nationwide web-based survey among all members of the Japanese Society of Child Neurology to identify pediatric patients aged < 18 years who developed acute encephalopathy in Japan between 1 January 2020 and 31 May 2022 associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection confirmed by polymerase chain reaction or antigen tests using pharyngeal swabs. Acute encephalopathy was defined as acute onset of impaired consciousness lasting > 24 h or an altered mental state; neurological symptoms arising within 2 weeks of onset of COVID-19 or multisystem inflammatory syndrome in children (MIS-C)/pediatric inflammatory multisystem syndrome (PIMS); evidence of SARS-CoV-2 infection; and reasonable exclusion of other diseases. Patients were divided into the known clinico-radiological acute encephalopathy syndrome group and unexplained or unclassifiable acute encephalopathy group. Outcomes were assessed by pediatric cerebral performance category (PCPC) score at hospital discharge. Results Of the 3,802 society members, 217 representing institutions responded, and 39 patients with suspected acute encephalopathy were reported, of which 31 met inclusion criteria. Of these patients, 14 were diagnosed with known clinico-radiological acute encephalopathy syndromes, with acute encephalopathy with biphasic seizures and late reduced diffusion (five patients) being the most common. Five developed acute encephalopathy associated with MIS-C/PIMS. Among 31 patients, 9 (29.0%) had severe sequelae or died (PCPC ≥ 4). Two of three patients with encephalopathy with acute fulminant cerebral edema and two with hemorrhagic shock and encephalopathy syndrome died. The PCPC scores were higher in the known clinico-radiological acute encephalopathy syndrome group than in the unexplained or unclassifiable acute encephalopathy group (P < 0.01). Discussion Acute encephalopathy related to SARS-CoV-2 infection was demonstrated to be more severe than that caused by other viruses in Japan. Acute encephalopathy syndromes characterized by specific neuroradiological findings was associated with poor clinical outcomes.